Prevalence of SARS-CoV-2 infection in the workplace: results of a year of investigation in the Marche Nord companies - Orlandi, Chiara; Orlandi, Chiara; Schiavano, Giuditta Fiorella; Brandi, Giorgio; Magnani, Mauro; Casabianca, Anna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The world of work has been profoundly affected by the COVID-19 pandemic since workplace activities involving close contact with coworkers and customers can lead to transmission of SARS-CoV-2 and compromise continuity of operations of workplaces. The Covid-Lab of University of Urbino and the Confindustria Pesaro Urbino association signed an agreement to support the Marche Nord companies in the adoption of anti-contagion safety protocols. Methods: Antibodies detection was performed using a rapid immunochromatographic test. Total RNA from nasopharyngeal swab was subjected to a real-time RT-PCR multiplex for the detection of RdRp specific gene and E gene of the SARS-CoV-2, and the internal control (human RNase P). Results: Between May 2020 and Apr 2021, over 10,000 rapid serological tests had been carried out on workers of 35 companies and in 5% of cases IgG or IgM were found (519). All the 519 swabs gave a valid result (RNAse P Ct≤40) with 105 positive results (20%) for SARS-CoV-2 with a Ct value ≤45. Overall, only 1% of samples resulted positive for viral RNA (105/10000). Conclusions: The University of Urbino set up a rapid-response (within 24 h, generally <6 h) diagnostic centre for SARS-CoV-2 detection (Covid-Lab) allowing the companies to activate the optimal safety path to ensure the health and safety of workers in the workplace. Our observations during this first year of activity, highlight that in the workplace, the infection does not seem to spread if precautionary measures are followed and only 1% (1 worker out of 100) tested positive for the SARS-CoV-2 virus.